(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A set ???? of vertices in a connected graph ???? = (????, ????) is called signal set of ???? if every vertex not in ???? lies on a signal path between vertices from ????. A signal number is the minimum cardinality of all signal sets in ????. In this paper, signal number of certain classes of graphs are determined and some of its general properties are obtained.